The Effect of Principal’s Leadership and Work Climate on Teacher’s Performance - Asrullah, Fahjri; Fitria, Happy; Puspita, Yenny (Journal of Social Work and Science Education, 2024)
The purpose of this study was to determine the effect of the principal’s leadership and work climate on the performance of junior high school teachers in Simpangkatis District, Central Bangka Regency. This type of research is a quantitative study with 76 respondents taken from all junior high school teachers in Simpangtis District. Data collection was carried out by distributing questionnaires using a 5-point Likert scale to measure 72 statement items. The data analysis technique used is descriptive and inferential statistical analysis with hypothesis testing using simple and multiple linear regression analysis. The results of the study show that: 1) there is an influence from the principal’s leadership on teacher’s performance; 2) there is an influence of the work climate on teacher’s performance; 3) there is an influence from the principal’s leadership and work climate on teacher’s performance with a contribution of 37.3%.